Implementation of reconfigurable galois field multipliers over2m using primitive polynomials - Raj Narain, B; T. Sasilatha, Dr (International Journal of Engineering and Technology, 2018)
The Galois field multiplier finds extensive use in cryptographic solutions and applications. The Galois field multiplier can be implemented as fixed bitwise or reconfigurable. For fixed length, the data is restricted to the fixed length. But in reconfigurable GF multipliers, the bit length of the multiplier is flexible and is independent of hardware architecture. This paper proposes a method to implement a reconfigurable GF multiplier for various bit values from 8 to 128 bits. This paper compares the area complexity of various bit size in Xilinx Spartan 3E family FPGA and estimates the resources required for the implementation.Â Â